Bacterial Dynamics of Hardaliye, a Fermented Grape Beverage, Determined by Highthroughput Sequencing - Muhammet Arıcı; Esra Yıldırım Servi; Halime Pehlivanoğlu; Banu Metin (Journal of Agricultural Sciences)
Hardaliye is a traditional beverage produced by fermenting red grapes with mustard seeds and sour cherry leaves in the Thrace region of Turkey. There are few studies that have determined the microorganisms responsible for hardaliye fermentation, and these are limited to lactic acid bacteria (LAB) using culture-dependent techniques. The aim of this study was to determine the bacterial dynamics of hardaliye fermentation using a culture-independent approach, high-throughput sequencing of 16S rRNA amplicons. Hardaliye was produced using the traditional method, and samples were taken and analyzed on days 0, 2, 4, 6, and 10 of fermentation. During the fermentation period, pH decreased from 3.65 to 3.23. Amplicon sequencing showed that bacterial diversity was highest at 2 d, and lowest at 10 d, the final day. Although Enterobacteriaceae was the most dominant family at 0 and 2 d, Acetobacteriaceae, specifically Gluconobacter frateurii, became dominant with ~50% relative abundance at 4 d, and increased its abundance to >98% at 6 and 10 d. Although a slight increase in the relative abundance of ~1% (0 d) to ~5% (4 d) was observed in LAB, their presence was limited. This study showed that acetic acid bacteria should not be overlooked in hardaliye fermentation.